Quantification of the demands during an ice-hockey game based on intensity zones determined from the incremental test outcomes - Stanula, A.; Gabrys, T.; Roczniok, R.; Szmatlan-Gabrys, U.; Ozimek, M.; Mostowik, A. (The Journal of Strength and Conditioning Research, 2016)
The purpose of this study was to determine ice-hockey players' playing intensity based on their heart rates (HRs) recorded during a game and on the outcomes of an incremental maximum oxygen uptake test. Sixteen ice-hockey players, members of the Polish national team junior (U20), performed an incremental test to assess their maximal oxygen uptake (VO2max) in the 2 week's period preceding 4 games they played at the World Championships. Players' HRs at the first and second ventilatory thresholds obtained during the test were used to determine intensity zones (low, moderate, and high) that were subsequently used to classify HR values recorded during each of the games. For individual intensity zones, the following HRs expressed as mean values and as percentages of the maximal heart rate (HRmax) were obtained: forwards, 143-151 b/min (HRmax, 75.2-79.5%), 152-176 b/min (HRmax, 80.0-92.4%), 177-190 b/min (HRmax, 92.9-100.0%); defensemen, 127-139 b/min (HRmax, 69.4-75.8%), 140-163 b/min (HRmax, 76.4-89.0%), 164-184 b/min (HRmax, 89.5-100.0%). The amounts of time the forwards and defensemen spent in the 3 intensity zones expressed as percentages of the total time of the game were the following: 58.75% vs. 44.29% (low), 21.95% vs. 25.84% (moderate), and 19.30% vs. 29.87% (high). The forwards spent average more time in the low-intensity zone than did the defensemen, with the difference being statistically significant in periods 1 and 2 (61.44% vs. 44.21% at p = 0.001 and 59.14% vs. 47.23% at p = 0.01, respectively). The results of the study indicate that a method using aerobic and anaerobic metabolism parameters to determine intensity zones can significantly improve the reliability of evaluation of the physiological demands of the game and can be a useful tool for coaches in managing the training process.